Islam nusantara: Islam dalam aliran sejarah Indonesia - Ilmiyah, Nahdliyatul (Maliki Interdisciplinary Journal, 2025)
This research aims to examine the development of Islam in Indonesia from the time of its emergence to its development in the social, political and legal contexts. Islam first entered Indonesia through trade routes, followed by the establishment of Islamic kingdoms in the region. In this process, Islam not only became a religion, but also shaped the structure of government and the legal system practiced in society. Modern movements that emerged in the 19th and 20th centuries also made important contributions to the renewal of religious thought and practice in Indonesia. Therefore, this research was conducted to understand the dynamics of Islamic history, especially related to the development of kingdoms, Islamic political orientation, Islamic legal institutions, and religious reform movements in Indonesia.